Effectiveness of pudendal nerve block in the management of acute post-hemorrhoidectomy pain in Asian individuals using inverse probability of treatment weighting (IPTW) - Chang-Cyuan Chen; Kuei-Ting Chang; Yuan-Wen Lee; Jian-Syun Chen; Po-Li Wei; Chia-Li Chang; Yan-Jiun Huang (Asian Journal of Surgery, 2025)
Background: Inadequate management of acute post-haemorrhoidectomy pain is a major concern. Optimal pain management is necessary to reduce acute postoperative pain and improve care quality. Therefore, we investigated the efficacy of postoperative pudendal nerve block (PNB) in reducing acute post-haemorrhoidectomy pain in Asian individuals. Methods: This retrospective cohort study analysed 108 adult patients with grade 3 haemorrhoids. Patients with anorectal cancer were excluded from this study. Among the 108 patients, 79 and 29 received spinal anaesthesia (SA) with PNB (SAPNB) and SA alone, respectively. Propensity score matching and inverse probability of treatment weighting were performed to adjust for the effects of confounders. Results: Patients receiving SAPNB had significantly lower postoperative pain scores 6, 12, and 18 h after haemorrhoidectomy but significantly higher postoperative pain scores 24 and 48 h after haemorrhoidectomy than did patients receiving SA alone. PNB, older age, female sex, reduced operation time, and absence of cardiovascular disease reduced the risk of moderate to severe postoperative pain. Only the addition of PNB was consistently associated with a reduced risk of moderate to severe pain 6, 12, and 18 h after haemorrhoidectomy. Patients receiving SAPNB had significantly lower risks of perianal swelling and urinary retention but a significantly higher risk of nausea than did those receiving SA alone. The two groups exhibited similarity in their rates of postoperative readmission because of poor pain management and their lengths of stay upon readmission. Conclusion: The addition of PNB to SA may effectively reduce acute post-haemorrhoidectomy pain.